The Impact of SDeaf Design Lab on Creative Design Skills of Deaf Students - Mei, Joei Ong Suk (Department of Special Education, 2023)
The SDeaf Design Lab was established under the Special Education Integration Program of SMK Taman Sutera, Johor. The lab provides a unique opportunity for deaf students to acquire creative skills in graphic design. It is an interactive, multi-sensory environment that allows students to engage with digital media to best develop their design creativity through assigned projects. This study aimed to investigate the impact of assigned projects on the creative design skills of deaf students. In this study, a qualitative focus group research method was used to explore the opinions, experiences, and attitudes of a group of 8 deaf students by having an in-depth discussion about the assigned projects they had worked on. Data were collected through the discussions with these 8 deaf students and the in-depth interviews with the 2 managers from the related graphic design industry. The results of this study demonstrate that the design projects assigned at the SDeaf Design Lab have a significant positive impact on the creative design skills of deaf students. These projects provide opportunities for self-expression, collaboration, and skill development while boosting confidence and preparing students for future professional endeavors in the field of graphic design.